The combined effect of training and match loads on injury risk in professional Australian footballers - Murray, N. B. (Australian Catholic University, 2018)
Australian football is a dynamic team sport, which requires players to perform a large number of high-intensity efforts, combined with low-intensity activities throughout a match. Due to the complex and unique demands of the sport, players require an adequate training stimulus to develop and enhance the physical qualities required to succeed at the highest level. The ability to develop physically challenging but appropriate training at an individual level to 1) enhance the technical and physical qualities required, and 2) minimise the negative response to training (i.e. injury, illness, etc.) is a crucial task for practitioners involved in the preparation of elite players.